2022
DOI: 10.1021/acsptsci.2c00005
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Preclinical Assessment of Sensory, Functional, Motivational-Affective, and Neurochemical Outcomes in Neuropathic Pain: The Case of the Sigma-1 Receptor

Abstract: Chronic pain remains a major health problem and is currently facing slow drug innovation. New drug treatments should address not only the sensory-discriminative but also functional and motivational-affective components of chronic pain. In a mouse model of neuropathic pain induced by partial sciatic nerve ligation (PSNL), we analyzed sensory and functional-like outcomes by hindpaw mechanical stimulation and automated gait analysis (CatWalk). We characterized over time a reward-seeking task based on diminished m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…Accordingly, other studies described a different time course of sensory and affective consequences of chronic pain. Affective ones develop later and last longer 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, other studies described a different time course of sensory and affective consequences of chronic pain. Affective ones develop later and last longer 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that negative affective-like changes produced by sciatic nerve injury appeared later than sensory changes (hypersensitivity to mechanical stimuli in the hind paw) and lasted longer . In the study, we observed changes in functional (gait analysis using the catwalk system) and affective dimensions at 6 weeks (using a highly palatable food reward-seeking task) that were associated with imbalances in monoaminergic function in the nucleus accumbens.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, in order to elucidate the underlying molecular mechanisms of the depressive resistant phenotype shown by σ 1 R –/– mice submitted to PSNL, we measured at week 6 postinjury the level of gene expression of important proteins involved in pain regulation and its associated affective disorders such as anxiety and depression at the central level. ,, We focus on identifying the altered expression of DAT and SERT as well as its corresponding rate-limiting enzymes, tyrosine hydroxylase (Th), and tryptophan hydroxylase 2 (Tph2). Additionally, we also analyzed the mRNA expression of BDNF, μ opioid receptor, and σ 1 R. Because sensory and affective changes were also observed in sham animals, we included naive animals in our study to better characterize the effects of surgery and direct sciatic nerve injury. ,, Assuming that the encoding of complex behavioral phenomena as depression induced by neuropathic pain involves coordinated gene expression in multiple brain regions, we analyzed, in the same experiment, transcription of genes across 10 structures associated with the limbic and mesolimbic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Both reflexive and nonreflexive pain behaviors were measured before histological processing. Nonreflexive responses provide complementary information about the overall impact of the persistent sensory abnormality [ 73 , 74 ]. The effect of BD1063 and pregabalin on both anxiety- and depression-like behaviors described in either RIM6 or ASI models [ 7 ] were also evaluated by means of the light/dark box and the forced swimming test, respectively.…”
Section: Resultsmentioning
confidence: 99%